2022
DOI: 10.1039/d1sm01334c
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-two-dimensional coalescence of nematic and isotropic droplets and Rayleigh–Plateau instability in flat optical cells

Abstract: Different coalescence regimes are observed for isotropic droplets in a nematic environment and nematic droplets in an isotropic environment in flat cells. Wetting conditions on the cell surfaces play a key role in the development of instabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The round, or even circular, meniscus profile was expected because of the small gap height of the Hele-Shaw cell (i.e., Bo < 1). Similarly, Dolganov et al found that the cross-sectional meniscus profile of a liquid crystal drop in a Hele-Shaw cell was close to circular [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The round, or even circular, meniscus profile was expected because of the small gap height of the Hele-Shaw cell (i.e., Bo < 1). Similarly, Dolganov et al found that the cross-sectional meniscus profile of a liquid crystal drop in a Hele-Shaw cell was close to circular [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to compare our experiment with the coalescence of isotropic droplets separated by a nematic bridge of the same material in flat cells. This scenario was studied by Dolganov et al 93,94 The situation is different there because the experiments were performed in Hele-Shaw cells. The presence of the upper and lower glass plates changes the situation completely.…”
Section: Conflicts Of Interestmentioning
confidence: 99%